1985
DOI: 10.1128/aem.49.5.1191-1196.1985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an activated sludge wastewater treatment plant on ambient air densities of aerosols containing bacteria and viruses

Abstract: Bacteriaand virus-containing aerosols were studied during the late summer and fall seasons in a midwestern suburb of the United States before and during the start-up and operation of an unenclosed activated sludge wastewater treatment plant. The study showed that the air in this suburban area contained low-level densities of indicator microorganisms. After the plant began operating, the densities of total aerobic bacteria-containing particles, standard plate count bacteria, total coliforms, fecal coliforms, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 16 publications
1
36
0
2
Order By: Relevance
“…The organisms isolated in the current study are common and are also a feature of other aerosol generating sites such as sewage treatment plants (via aerosol droplets) (Adams and Spendlove 1970;Fannin et al 1985). A long-term waste water plant operation showed high bacterial (coliforms, E. coli and staphylococci) and fungal concentrations in almost all of the sites around the plant including downwind positions (Brandi et al 2000) as in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…The organisms isolated in the current study are common and are also a feature of other aerosol generating sites such as sewage treatment plants (via aerosol droplets) (Adams and Spendlove 1970;Fannin et al 1985). A long-term waste water plant operation showed high bacterial (coliforms, E. coli and staphylococci) and fungal concentrations in almost all of the sites around the plant including downwind positions (Brandi et al 2000) as in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…It has been reported that aerosols are capable of transporting micro-organisms over long distances (Bovallius et al 1978) and, depending on the source, that they may be able to produce infections (Fraser 1980;Sattar and Ijaz 1987), asthmatic problems (Gravesen 1979) and other health effects (Jacobs 1989;Burrel 1990) in susceptible subjects. The aeration tanks of wastewater treatment plants are recognized as important sources of microbial aerosols (Napolitano and Rowe 1966;Kenline and Scarpino 1972;Cannon 1983;Fannin et al 1985) and therefore might be hazardous for exposed subjects, ®rstly for plant workers as a consequence of direct contact with the contaminated materials/substrates or by inhalation of aerosolized microorganisms. Moreover, a potential risk for visitors to the plants and for the surrounding population cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a potential risk for visitors to the plants and for the surrounding population cannot be excluded. Various potentially infectious agents have frequently been recovered from the air around wastewater plants (Hickey and Parker 1975;Millner et al 1980;Fannin et al 1985) and a high prevalence of antibodies against several enteric viruses has been found in exposed subjects (Clark 1981a;Heng et al 1994), although this is not necessarily related to aerosols. Clear evidence of the adverse health effects caused by exposure to micro-organism-containing aerosols, however, has not yet been presented in a satisfactory manner (Clark et al 1981b;Stener 1986;Maguire 1993), and as far as is known, outbreaks due to aerosols generated during the wastewater treatment process have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, coliforms are of questionable validity as markers of viral contamination of air (Teltsch et al 1980), and coliphage have therefore been suggested as a better index (Fannin et al 1985). In this respect, bacteriophage such as those employed in this study may, under some circumstances, be superior to suggested bacterial tracers of airborne contamination (Sattar et al 1982).…”
Section: Discussionmentioning
confidence: 87%
“…There is good evidence that bacteriophage are more stable during airborne transport than either indicator bacteria or poliovirus (Fannin et al 1985). In this study, three bacteriophage tracers were used in order to allow for differences in stability and recovery efficiency.…”
Section: Discussionmentioning
confidence: 99%